Aṉupōka vaittiya navanītam - Aptullā Cāyapu, Pā. Mukammatu (Veḷiyīṭṭut toṭar (Aruḷmiku Paḻani Taṇṭāyutapāṇi Cuvāmi Tirukkōyil. Citta Maruttuvanūl Veḷiyīṭṭuk Kuḻu), 1975)
Critical edition of prescriptions for the treatment of diseases, according to the Siddha system of Indic medicine.